Pharmacokinetics and Comparative Bioavailability Study of Two Clarithromycin Suspensions Following Administration of a Single Oral Dose to Healthy Volunteers - Zakeri-Milani, Parvin; Valizadeh, Hadi; Ghanbarzadeh, Saeed; Nemati, Mahboob (Arzneimittelforschung, 2009)
The aim of the present study was to compare the pharmacokinetics and bioavailability of two commercial brands of clarithromycin (CAS 81103-11-9) suspensions in healthy male Iranian volunteers. In an open label, single-dose, randomized study with a crossover design an equivalent 500-mg clarithromycin suspension was given orally to each of 24 subjects as a single dose on two treatment days. The treatment periods were separated by a one-week washout period. Blood samples were drawn at different time points and the separated plasma was kept frozen at −20 °C for subsequent analysis. The plasma concentrations of the drug were analyzed by a rapid and sensitive HPLC method with UV detection.Mean maximum serum concentrations of 2 256.5 ± 590.1 ng/mL and 2 840.2 ± 717.5 ng/mL were obtained for the test and reference formulation, respectively. The AUC0–infinity of clarithromycin was on average 45 008.7 ± 10 989.9 ng · h/mL for the test and 45 221.3 ± 2155.7 ng h/mL for the reference formulation. The calculated 90% confidence intervals for the ratio of Cmax (81.98–94.26%), (91.6–109.15%) and (93.08–110.85%) values for the test and reference products were all within the 85–120% interval proposed by the FDA and EMEA. Therefore the clarithromycin suspension of the test and reference formulations are bioequivalent in terms of rate and extent of absorption.
Keywords: CAS 81103-11-9; Clarithromycin, bioavailability, bioequivalence, pharmacokinetics; Klarexir®; Macrolide antibiotic